Recognition of Earthquake-Prone Areas in the Himalaya: Validity of the Results - A. Gorshkov; I. A. Parvez; O. Novikova (International Journal of Geophysics)
In 1992 seismogenic nodes prone for earthquakes 6.5+ have been recognized for the Himalayan arc using the pattern recognition approach. Since then four earthquakes of the target magnitudes occurred in the region. The paper discusses the correlation of the events occurred in the region after 1992 with nodes previously defined as having potential for the occurrence of earthquakes M6.5+. The analysis performed has shown that three out of four earthquakes M6.5+ occurred at recognized seismogenic nodes capable of M6.5+.